Regulatory aspects of human radiolabeled mass balance studies in oncology: concise review. (2nd April 2016) - Nijenhuis, C. M.; Schellens, J. H. M.; Beijnen, J. H.
Abstract: Human radiolabeled mass balance studies are performed to obtain information about the absorption, distribution, metabolism, and excretion of a drug in development. The main goals are to determine the route of elimination and major metabolic pathways. This review provides an overview of the current regulatory guidelines concerning human radiolabeled mass balance studies and discusses scientific trends seen in the last decade with a focus on mass balance studies of anticancer drugs. This paper also provides an overview of mass balance studies of anticancer agents that were executed in the last 10 years.